PENGARUH MUSIK DAN LINGKUNGAN BELAJAR TERHADAP SISWA - ZAMIL, ILHAM (Pelita Bangsa Pelestari Pancasila, 2016)
Learning requires a proper learning atmosphere so that learning objectives can be achieved. The right learning environment can be seen from the learning environment. The learning environment should be designed as comfortable as possible so that students can follow the lessons well. Conducive learning environment needs to be created by teachers. Create a learning environment can use many methods, one of which is to use the music. This refers to the type of student learning is the type of audio learning, the type of learning that use certain music. Conducive learning environment and the use of certain music contribute to the implementation of learning.